Кадирбекова А.А., Сабденбекова Г.Т., Оспанова А.С., Казова Р.А., Ленчке Я. Моделирование закономерностей влияния аэрополлютантов на степень очистки выбросов предприятия: 1Казахский национальный исследовательский технический университет имени К.И. Сатпаева, Казахстан, г. Алматы 2ЧУ Политехнический колледж корпорации «Казахмыс», Казахстан, г. Балхаш 3Берлинский университет Гумбольдта, Германия, г. Берлин *e-mail: zhaku84@mail.ru (Eurasian Journal of Ecology, 2017)
In accordance with results of the monitoring was doing fulfilment the mathematical planning ofprocess of purifying of emissions on the enterprise and defined the optimal conditions of catching soiling substances. It was used method of planning of experiments, which based on the non-linear multiplycorrelation. On the basis of Latin squares created of matricx the mathematical planning and given levels(p) of studied factors (usually p=5). The structure of the matrix is such, that if fulfil all experiments inaccordance to plane n= p2, numbers of experiments (n) will n=52 i.e. n=25 and of level any factor hascombination with level of other factor only one time. The criterion of completeness current of process isdegree interaction. In the ecology – degree of soiling of environment, in technology – is degree of turning of initial substances with forming ended product, degree crystallization et ctr. The analysis of modules for mathematical description of the functions is done.Analyses of the privatefunctions shoved, that the most effusion and strong influencing factors are concentration of the inorganicdust (Х1), duration of interaction (Х3) and temperature of environment (Х4).Key words: modeling, multiple correlation, factor, air pollutant, matrix of planning, degree of pollution, levels of factors, private dependence.